2019
DOI: 10.1073/pnas.1809913116
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of O 2 with a diiron protein generates a mixed-valent Fe 2+ /Fe 3+ center and peroxide

Abstract: The gene encoding the cyanobacterial ferritinSynFtn is up-regulated in response to copper stress. Here, we show that, whileSynFtn does not interact directly with copper, it is highly unusual in several ways. First, its catalytic diiron ferroxidase center is unlike those of all other characterized prokaryotic ferritins and instead resembles an animal H-chain ferritin center. Second, as demonstrated by kinetic, spectroscopic, and high-resolution X-ray crystallographic data, reaction of O2with the di-Fe2+center r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…A bacterial ferritin, called SynFtn, isolated from the coastal marine cyanobacterium Synechococcus strain CC9311 was recently shown to be unusual in that it more closely resembles eukaryotic H-chain ferritins than previously studied Ftn proteins. 18 This study demonstrated that SynFtn oxidises iron via a mechanism that is unique among diiron proteins characterised to date. The protein as isolated was free from metal ions.…”
Section: Introductionmentioning
confidence: 76%
“…A bacterial ferritin, called SynFtn, isolated from the coastal marine cyanobacterium Synechococcus strain CC9311 was recently shown to be unusual in that it more closely resembles eukaryotic H-chain ferritins than previously studied Ftn proteins. 18 This study demonstrated that SynFtn oxidises iron via a mechanism that is unique among diiron proteins characterised to date. The protein as isolated was free from metal ions.…”
Section: Introductionmentioning
confidence: 76%
“…We suggest that ferritin paralogs likewise have distinct functions such as managing intracellular, extracellular and/or diel fluctuations in Fe levels (Botebol et al ., ). For example, ferritin paralog GC_00028B in coastal strain CC9311 was recently suggested to play a novel role in metal detoxification based on structural and biochemical analysis (Bradley et al ., ). Consistent with this, the paralog was most abundant at sites with intermediate levels of Fe (0.3–1 nM) that also likely have higher concentrations of other toxic metals.…”
Section: Discussionmentioning
confidence: 97%
“…Metal ions play a crucial role in environmental and biological systems. Fe 3+ , one of the most essential transition metal ions, is indispensable for biochemical processes at cellular level . Excess and deficiency of Fe 3+ would impair biological systems seriously .…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3+ , one of the most essential transition metal ions, is indispensable for biochemical processes at cellular level . Excess and deficiency of Fe 3+ would impair biological systems seriously . Iron deficiency would cause anemia, decreased immunity, liver, heart and kidney damages, while Parkinson's and Alzheimer's diseases are related to iron surplus .…”
Section: Introductionmentioning
confidence: 99%